The Analysis of Figurative Language in Taylor Swift’s Lover Album - Lutfiah Al Karimah; Christina M. Hum (Metaphor, 2025)
This thesis explores the types and functions of figurative language in the Lover album on the Spotify platform. Figurative language is a style of language that is not conveyed directly, but rather through beautiful and meaningful ways to reinforce the message and convey feelings more emotionally. The study identifies various types of figurative language, including similes, metaphors, personification, symbolism, metonymy, apostrophe, and others. These are used not only to enrich the poetic quality of the lyrics but also to deliver deeper meanings. The functions of figurative language are observed to create vivid imagery, to make abstract ideas more concrete, to emphasize important ideas, and to add emotional intensity. The study concludes that Taylor Swift uses figurative language to convey complex feelings and themes of life that many people can relate to in beautiful songs.